1999
DOI: 10.1039/a809882d
|View full text |Cite
|
Sign up to set email alerts
|

The molecular structures of 2-, 3- and 4-chloropyridine and chloropyrazine in the gas phase by electron diffraction and ab initio calculations †

Abstract: The gas-phase molecular structures of chloropyrazine, 2-, 3-and 4-chloropyridine have been determined by ab initio calculations and by gas-phase electron diffraction (GED) supplemented with rotation constants and restraints based on ab initio calculations. Geometries are compared to those of their respective parent compounds and other related systems to demonstrate the effects of chlorination on ring geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It is seen from the tables that the theoretically calculated gas-phase data of the bond lengths and bond angles for both 2Clpy and 3Clpy agree nicely with the experimental data reported by Smart et al 36 The only disagreement observed is in the length of the C-Cl bond. The B3LYP/6-31CG(d,p) method seems to work precisely for these systems.…”
Section: Geometrical Structure and Interaction Energiessupporting
confidence: 77%
See 1 more Smart Citation
“…It is seen from the tables that the theoretically calculated gas-phase data of the bond lengths and bond angles for both 2Clpy and 3Clpy agree nicely with the experimental data reported by Smart et al 36 The only disagreement observed is in the length of the C-Cl bond. The B3LYP/6-31CG(d,p) method seems to work precisely for these systems.…”
Section: Geometrical Structure and Interaction Energiessupporting
confidence: 77%
“…9 Vibrational dephasing of the C-Cl stretching mode of 2Clpy and 3Clpy in a methanol environment was carried out using polarized Raman and DFT calculations. 10 As explained by Torri, 11,12 the dipole derivative (υµ m /υq m ) is enhanced upon hydrogen bonding and consequently the infrared (IR) intensity, being proportional to (υµ m /υq m ), 2 becomes stronger owing to the interaction with the electric field of the surrounding molecules.…”
Section: Introductionmentioning
confidence: 99%